Compressibility Behavior Of Tropical Peat Reinforced With Cement Column - Duraisamy, Youventharan (2008)

(untitled)
One of the most serious problems encountered by civil engineers these days are when it comes to construction on peat soil. Peat soil poses a difficult problem, which has the tendency to subside especially when its moisture content is high. The moisture content may come from rain flooding, leaking from water or sewer lines or from reduction in surface evapo-transpiration when an area is covered by building or pavement. Peat soil causes cracking, settlements and break-up of pavements, railways, highways, embankments, roadways, building foundations, reservoir linings, water lines and sewer line. These entire problems can be solved if the engineering properties of the problem soil are improved to make them suitable for construction. The main objective of this research is to evaluate the effect of cement column on compressibility when installed in peat soil. Apart from that the researcher also found it important to examine the peculiar engineering behaviour of tropical peat with respect to their compressibility characteristics due to variation in fiber content and organic content In addition, the researcher is also interested to identify the influences of other factors like diameter, length, curing time, number of cement columns and amount of cement in cement columns in reducing compressibility. Undisturbed sample of peat soils were taken from Banting, which is situated in the West coast of Peninsular Malaysia. A suitable auger was designed and fabricated to collect undisturbed peat sample of 150 mm diameter and 230 mm in length. Specimens with 45 mm diameter (area ratio = 0.09) and 60 mm diameter (area ratio = 0.16) of cement column were cured for 7, 14 and 28 days, after which they were subjected to Rowe Cell consolidation test. Results are also presented from test conducted on groups of cement columns using four (area ratio = 0.04) and nine (area ratio = 0.09) columns of 15 mm diameter each to investigate the influence of number of cement columns on compressibility of peat soil. Based on the results obtained, it shows that the cement columns can successfully reduce the compressibility of tropical peat. Compression index of fibric sample was reduced by 60% using cement column of 45 mm diameter and 80% with cement column of 60 mm diameter. Hence, it suggests that larger diameter cement column (or high area ratio) has a higher reduction effect in the compression index. The trend is similar in hemic and sapric peat. A group of cement columns had a significant impact in reducing the compressibility parameters compared to a single cement column due to higher surface area. Using 100% amount of cement in columns recorded the best performance. Compressibility parameters (compression index and coefficient of secondary compression) were significantly improved (lowered) with cement column.